1996
DOI: 10.1016/0014-5793(96)00300-6
|View full text |Cite
|
Sign up to set email alerts
|

Identification of cyclic AMP‐phosphodiesterase variants from the PDE4D gene expressed in human peripheral mononuclear cells

Abstract: To determine whether the expression of different PDE4D variants is unique to the rat or conserved through evolution, we have characterized the different PDE4D mRNAs expressed in human peripheral blood mononuclear cells. RT-PCR was performed using primers based on rat sequences and mRNAs from mononuclear cells. The specifically amplified fragments had a size identical to that predicted for rat PDEAD1, PDE4D2 and PDE4D3. Sequencing confirmed that these fragments are derived from the human PDE4D gene. Their seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
32
1

Year Published

1996
1996
2008
2008

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 39 publications
(58 reference statements)
6
32
1
Order By: Relevance
“…The structure of these cDNAs demonstrate that transcripts from the PDE4D gene undergo a complex pattern of alternative splicing, which resembles that of transcripts from the D. melanogaster dunce gene. Our data demonstrate that the PDE4D gene has a more complex structure than that reported previously [13,16]. We have also studied the biochemical properties of the various PDE4D isoforms, and for this purpose utilized a single system, expression in mammalian COS-7 cells, in which the properties of the five individual isoforms could be compared.…”
Section: Introductionmentioning
confidence: 60%
See 3 more Smart Citations
“…The structure of these cDNAs demonstrate that transcripts from the PDE4D gene undergo a complex pattern of alternative splicing, which resembles that of transcripts from the D. melanogaster dunce gene. Our data demonstrate that the PDE4D gene has a more complex structure than that reported previously [13,16]. We have also studied the biochemical properties of the various PDE4D isoforms, and for this purpose utilized a single system, expression in mammalian COS-7 cells, in which the properties of the five individual isoforms could be compared.…”
Section: Introductionmentioning
confidence: 60%
“…For example, the deduced amino acid sequences of the proteins encoded by pDun411 and pPDE82 are identical with those of the human PDE4D1 and PDE4D2 isoforms respectively cloned by PCR by Nemoz et al [13]. The truncated human PDE4D cDNA isolated by Baecker et al [36] could represent any of our pPDE43, pPDE39 or pPDE79 cDNAs.…”
Section: Cdna Clones Corresponding To Transcripts From the Human Pde4mentioning
confidence: 79%
See 2 more Smart Citations
“…It has been reported that one subtype of the PDE4 subfamily, PDE4D, is activated by phosphorylation with A-kinase, and the PDE4D gene of the rat codes for at least three alternative splicing variants; ratPDE3.1(PDE4D 1), ratPDE3.2(PDFAD2) and ratPDE3.3(PDE4D3) (25,26). Only ratPDE3.3(PDE4D3) has been phosphorylated by A-kinase to be activated in a eeU free system (25).…”
Section: Resultsmentioning
confidence: 99%